Vulnerability Assessment of Building Frames Subjected to Progressive Collapse Caused by Earthquake - Mohamed Nazri, Fadzli; Zolkifle, Mohamad Khairi Adha; Mansor, Hazrina; Shahidan, Shahiron (EDP Sciences, 2017)
Progressive collapse is an initial local failure of the structural component and leading to the additional collapse of the building frames. This study investigated the vulnerability of four- and six-storey moment resisting concrete frame (MRCF) buildings subjected to progressive collapse. The four- and six-storey MRCF buildings were designed based on British Standard (BS) and Eurocode (EC). The differences between these two codes were investigated. Nonlinear static analysis, which is also known as pushover analysis (POA), and nonlinear dynamic analysis or incremental dynamic analysis (IDA), were performed for each model to obtain capacity curve and explore vulnerability measures. IDA was conducted using a sample of ground motion from an earthquake that occurred in Ranau, Sabah in 2015. The four-storey building was more vulnerable than the six-storey building.